Penerapan Ais Transponder untuk Keselamatan Kapal Nelayan - Supria, Supria; Romadhoni; Isna Yulia; Marzuarman; M Afridon; Hardiyanto (ABEC Indonesia, 2023)
Fishermen in the Bengkalis Strait are one of the livelihoods of the Bengkalis residents. Many fishermen who go on cruises do not apply traffic rules in the waters so that accidents often occur in the waters. In this study, it is proposed to apply AIS Transponder for monitoring the security and safety of ships around Bengkalis waters. The developed AIS Transponder is capable of sending and receiving AIS data installed on ships. From the results of the trials that have been carried out, it shows that the AIS transponder can transmit AIS data to the Polbeng AIS receiver and can track nearby ships that have AIS devices.